Job Satisfaction and Turnover Intention Among People With Disabilities Working in Special Employment Centers: The Moderation Effect of Organizational Commitment - Romeo, Marina; Yepes-Baldó, Montserrat; Lins, Claudia (Frontiers in Psychology, 2020)
With the goal of contributing to the growth of research on people with disabilities in employment, in particular in relation to their job satisfaction (JS), organizational commitment (OC) and turnover intention (TI), this study explores the effect of job satisfaction on turnover intention among employees with disabilities, and the moderation effect of organizational commitment and its four dimensions on this main relationship. A total of 245 Special Employment Center (SECs) employees in Spain answered a questionnaire. To analyze the results a descriptive analysis with bivariate correlations across the variables was performed, and the moderation model was tested subsequently using macro PROCESS for SPSS by Hayes. For the significant effects, a pick-a-point approximation was used to interpret the results. The results show that organizational commitment and its dimensions have no significant effect on the direct relationship. However, some components of job satisfaction, such as the relationship with co-workers and with supervisors, play a significant role in the relationship with turnover intention when moderated by affective and value commitment. Our results show that it is important that human resources departments create conditions favoring a work environment with positive interpersonal relationships between employees and managers in order to minimize turnover intention at SECs.